Development of KM-60 Based Orbit Control Propulsion Subsystem for Geostationary Satellite. (2017) - Vorontsov, V.V.; Kostin, A.N.; Lovtsov, A.S.; Volkov, D.V.; Ermoshkin, Yu. M.; Yakimov, E.N.; Gorshkov, O.A.; Ostapushchenko, A.A.; Udalov, D.V.; Arkhipov, Yu. S.; Buldashev, S.A.
Abstract: The paper contains the development results of an orbit-control electric jet propulsion subsystem intended for a geostationary satellite based on the EXPRESS-1000 family medium class platform. The subsystem is based on the newly-developed KM-60 thrusters featuring an increased specific pulse, and equipped with a Xenon storage tank made of composites, a small-sized Xenon feed unit, PPU and dedicated software. During the development stage, scientific and technical tasks were carried out to ensure thruster performance stability over the lifetime, to create a power processing system featuring increased output voltage, and a control unit operating through a multiplex data bus. As a result, a thruster subsystem significantly exceeding similar subsystems in main parameters was developed and implemented.